Genome Evolution of Two Genetically Homogeneous Infectious Bursal Disease Virus Strains During Passages in vitro and ex vivo in the Presence of a Mutagenic Nucleoside Analog - Cubas-Gaona, Liliana L.; Flageul, Alexandre; Courtillon, Céline; Briand, Francois-Xavier; Contrant, Maud; Bougeard, Stephanie; Lucas, Pierrick; Quenault, Hélène; Leroux, Aurélie; Keita, Alassane; Amelot, Michel; Grasland, Béatrice; et al. (Frontiers in Microbiology, 2021)
The avibirnavirus infectious bursal disease virus (IBDV) is responsible for a highly contagious and sometimes lethal disease of chickens (Gallus gallus). IBDV genetic variation is well-described for both field and live-attenuated vaccine strains, however the dynamics and selective constraints behind this genetic evolution remain poorly documented. Here, genetically homogeneous virus stocks were generated using reverse genetics for a very virulent strain, rvv, and a vaccine-related strain, rCu-1. These viruses were serially passaged at controlled multiplicities of infection in several biological systems, including primary chickens B cells, the main cell type targeted by IBDV in vivo. Passages were also performed in the absence or presence of a strong selective pressure using the antiviral base analog 7-deaza-2'-C-methyladenosine (7DMA). Next Generation Sequencing (NGS) of viral genomes after the last passage in each biological system revealed that i) a higher viral diversity was generated in segment A than in segment B, regardless 7DMA treatment and viral strain, ii) diversity in segment B was increased by 7DMA treatment in both viruses , iii) passaging of IBDV in primary chicken B cells, regardless of 7DMA treatment, did not select cell-culture adapted variants of rvv, preserving its capsid protein (VP2) properties, iv) mutations in coding and non-coding regions of rCu-1 segment A could potentially associate to higher viral fitness and v) a specific selection, upon 7DMA addition, of a Thr329Ala substitution occurred in the viral polymerase VP1. The latter change, together with Ala270Thr change in VP2, proved to be associated with viral attenuation in vivo. These results identify genome sequences that are important for IBDV evolution in response to selective constraints. Such information will help tailor better strategies for controlling IBDV infection in chickens.